3D animation for the raw beginner using Autodesk Maya - King, Roger (Roger Alan) (CRC Press/Taylor & Francis Group, 2019)
"3D Animation for the Raw Beginner Using Maya is an ideal academic textbook as well as a superlative do-it-yourself training manual. When employed as a text, it frees the instructor from the painstaking task of developing step-by-step examples to present Maya's complex interface and basic capabilities. When used for individual study, aspiring animators revel in the book's easy-tofollow, hands-on learning style"-- Provided by publisher
Includes index
Keywords: Computer animation -- Amateurs' manuals; Three-dimensional display systems -- Amateurs' manuals